2018
DOI: 10.1051/0004-6361/201833499
|View full text |Cite
|
Sign up to set email alerts
|

NELIOTA: The wide-field, high-cadence, lunar monitoring system at the prime focus of the Kryoneri telescope

Abstract: We present the technical specifications and first results of the ESA-funded, lunar monitoring project "NELIOTA" (NEO Lunar Impacts and Optical TrAnsients) at the National Observatory of Athens, which aims to determine the size-frequency distribution of small Near-Earth Objects (NEOs) via detection of impact flashes on the surface of the Moon. For the purposes of this project a twin camera instrument was specially designed and installed at the 1.2 m Kryoneri telescope utilizing the fast-frame capabilities of sc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 29 publications
0
25
0
2
Order By: Relevance
“…A.5), duration and the calibrated peak magnitudes in R and I bands. Unfortunately, as it is derived by Xilouris et al (2018) and Liakos et al (2020), the reported magnitudes and errors on the NELIOTA database are approximate, while some selenographic coordinates are possibly reported incorrectly (swapped longitude and latitude).…”
Section: Neliotamentioning
confidence: 96%
See 3 more Smart Citations
“…A.5), duration and the calibrated peak magnitudes in R and I bands. Unfortunately, as it is derived by Xilouris et al (2018) and Liakos et al (2020), the reported magnitudes and errors on the NELIOTA database are approximate, while some selenographic coordinates are possibly reported incorrectly (swapped longitude and latitude).…”
Section: Neliotamentioning
confidence: 96%
“…In this work we follow the same assumptions and methodology that are described in details by Avdellidou & Vaubaillon (2019) and here we remind the main steps. According to Xilouris et al (2018) the NELIOTA magnitudes R and I are calibrated in the Cousins system and the R − I colour is described by the the following equations:…”
Section: Neliotamentioning
confidence: 99%
See 2 more Smart Citations
“…MIDAS was the first of such monitor system confirming the L1-21J event. More recently, the NEO Lunar Impacts and Optical TrAnsients, NELIOTA saw the first light [22]. To date at least 55 flashes have been registered by the NELIOTA team, most of them produced by sporadic impactors and some by geminids.…”
Section: (Exactly One Metonic Cycle Ago)mentioning
confidence: 99%